ANALYSIS OF NUMERICAL LITERACY SKILLS OF CLASS VIII STUDENTS OF ACCREDITED SMP A IN RAPPOCINI SUB-DISTRICT - Magfira Magfira; Muh Tawil; Salma Samputri (Universitas Negeri Makassar, 2024)
This study aims to analyze the high level of numerical literacy skills of grade VIII students in accredited public and private junior high schools in Rappocini District. This research is a quantitative descriptive survey with a population of 1080 students and a sample of 292 students selected randomly. The research instrument was a 10 question multiple choice test. Data were analyzed descriptively and inferentially. The results showed: (1) the numerical literacy ability of public junior high school students is in the medium category (53.48%), (2) the ability of private junior high school students is in the high category (69.03%), (3) indicators of knowing, applying, and reasoning in public junior high schools are in the medium category (54.67%, 49.13%, and 56.62%), (4) indicators in private junior high schools are in the high category (69.35%, 72.04%, and 65.59%), (5) the average numerical literacy skills of public junior high school students are 5-6 (medium category) and private junior high school students are 6-7 (high category), (6) there is a significant difference between the numerical literacy skills of public and private junior high school students.